Cholinergic neurons—keeping check on amyloid β in the cerebral cortex - Ovsepian, Saak V.; Herms, Jochen (Frontiers in Cellular Neuroscience, 2013)
The physiological relevance of p75 neurotrophin receptor-mediated internalization of ligands with no apparent trophic functions by nerve cells remains unclear. Herein, we propose a homeostatic role for this in clearance of amyloid β (Aβ) in the brain. We hypothesize that uptake of Aβ in conjunction with p75NTR followed by its degradation in lysosomes endows cholinergic basalo-cortical projections enriched in this receptor a capacity for maintaining physiological levels of this peptide in target areas. Thus, in addition to the diffuse modulator influence and channeling of extra-thalamic signals, cholinergic innervations could supply the cerebral cortex with an elaborate system for Aβ drainage. Interpreting the emerging relationship of molecular data with recognized role of cholinergic modulator system in regulating cortical activity should provide new insights into the brain physiology and mechanisms of neuro-degenerative diseases.